PEMIKIRAN PENDIDIKAN ISLAM MENURUT HAMKA - Sukari Sukari (MAMBA'UL 'ULUM, 2021)
That the current moral collapse is due to the values ​​of honesty, truth, justice, please help, and compassion have been replaced by misuse, oppression, tackle each other, deception, and mutual harm. So much slander and fighting sheep, licking, corruption, and many other disobedience. The description of social violations occurring in this nation opens space to reflect on the extent to which formal education efforts, which are nationally organized institutions, educate, direct and guide students in a normative way. Because in his view that education is a means of educating personal character. As an Islamic Figure, Hamka's views on Islamic education are very deep. According to Hamka, education is the parents' religious guidance for children by: helping humans to obtain a decent living, but more than that, with human knowledge, they will be able to know their God, refine their morals, and always try to seek the pleasure of God. Therefore, the purpose of education is to serve and worship Him. Therefore, in educational material must include the following three things, namely: science, charity, morals and justice. So we should appreciate Buya Hamka's efforts to participate in developing the intellectual life of the nation by applying its views on education. He founded the Al-Azhar Foundation, which has spread its branches throughout Indonesia.